2022
DOI: 10.1158/1538-7445.am2022-ct008
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT008: Long-term outcomes with sotorasib in pretreated KRASp.G12C-mutated NSCLC: 2-year analysis of CodeBreaK100

Abstract: Introduction: Sotorasib, a first-in-class KRASG12C inhibitor, has been FDA-approved for adults with KRAS p.G12C-mutated locally advanced or metastatic NSCLC who received prior systemic therapies based on the Phase 1/2 global, single-arm CodeBreaK100 trial. We will report the longest follow-up for a KRASG12C inhibitor, including 2-year survival, safety, and genomic profiles associated with durable clinical benefit. Methods: Sotorasib was administered orally at 960 mg once daily to patients who pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Nevertheless, future clinical efficacy in KRAS G12C-mutant PEAC might be achieved by sotorasib, as shown by the latest data of CodeBreaK100 study. 34 Moreover, EGFR sensitive mutations were exclusively found in five PEAC patients, which is similar to a previous Chinese report on PEAC. 35 Less frequent EGFR mutations have been described in other European studies possibly due to different mutation profiles across ethnic groups.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, future clinical efficacy in KRAS G12C-mutant PEAC might be achieved by sotorasib, as shown by the latest data of CodeBreaK100 study. 34 Moreover, EGFR sensitive mutations were exclusively found in five PEAC patients, which is similar to a previous Chinese report on PEAC. 35 Less frequent EGFR mutations have been described in other European studies possibly due to different mutation profiles across ethnic groups.…”
Section: Discussionsupporting
confidence: 88%
“…Grade 3 and grade 4 TRAEs were reported in 20% and 1% of patients, respectively, and no fatal TRAEs were reported. 15 …”
Section: The Breakthrough In Targeted Therapy For Kras G12c-mutant Nsclcmentioning
confidence: 99%
“…Grade 3 and grade 4 TRAEs were reported in 20% and 1% of patients, respectively, and no fatal TRAEs were reported. 15 Furthermore, the global Phase III study (CodeBreak 200) of sotorasib versus docetaxel for previously treated NSCLC with KRAS G12C mutation was published by the European Society for Medical Oncology (ESMO) in 2022. 16 The results showed that sotorasib significantly improved the primary endpoint of PFS compared to docetaxel (5.6 vs 4.5 months, HR=0.66, p=0.002).…”
mentioning
confidence: 99%
“… 50 An updated ORR from combining phases I and II NSCLC patients ( n = 174) was 40.7% [95% confidence interval (CI): 33.2–48.4] and median progression-free survival (PFS) and overall survival were 6.3 months (95% CI: 5.3–8.2) and 12.5 months (95% CI: 10.5–17.8), respectively. 51 …”
Section: Introductionmentioning
confidence: 99%